White matter dissection with the Klingler technique: a literature review - Dziedzic, Tomasz A.; Balasa, Artur; Jeżewski, Mateusz P.; Michałowski, Łukasz; Marchel, Andrzej (Brain Structure and Function, 2021)
The aim of this literature review is to present a summary of the published literature relating the details of the different modifications of specimen preparation for white matter dissection with the Klingler technique. For this review, 3 independent investigators performed an electronic literature search that was carried out in the Pubmed, Scopus and Web of Science databses up to December 2019. Furthermore, we performed citation tracking for the articles missed in the initial search. Studies were eligible for inclusion when they reported details of at least the first 2 main steps of Klingler’s technique: fixation and freezing. A total of 37 full-text articles were included in the analysis. We included original anatomical studies in which human white matter dissection was performed for study purposes. The main three steps of preparation are the same in each laboratory, but the details of each vary between studies. Ten percent formalin is the most commonly used (34 studies) solution for fixation. The freezing time varied between 8 h and a month, and the temperature varied from − 5 to − 80 °C. After thawing and during dissections, the specimens were most often kept in formalin solution (13), and the concentration varied from 4 to 10%. Klingler’s preparation technique involves three main steps: fixation, freezing and thawing. Even though the details of the technique are different in most of the studies, all provide subjectively good quality specimens for anatomical dissections and studies.